The feasibility study on Clean Development Mechanism (CDM) in Malaysia: article / Aisyah Nur Addia Azizan and Syafiza Abd Hashib - Azizan, Aisyah Nur Addia; Abd Hashib, Syafiza (2018)
The Clean Development Mechanism require the Annex 1 countries to assist Non Annex 1 countries in achieving sustainable development in addition to its function as an emission reduction compliance mechanism for the Annex 1 country parties. Malaysian industries has familiarise with the clean development mechanism and started to register in order to join the sustainable development. This study includes the statistic of Malaysia’s projects registered so far, and reviewing the project design document of waste handling and disposal projects. A survey on sustainability is conducted and shows that the organizations in Malaysia are aware of sustainable development.